ANALISIS SPASIAL FAKTOR LINGKUNGAN DENGAN KEJADIAN MALARIA DI WILAYAH KERJA PUSKESMAS SALAMAN I, KABUPATEN MAGELANG - Wardah Wardah; Nurjazuli Nurjazuli; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2017)
Malaria is still a public health problem in the world including Indonesia. Magelang regency is one of the areas in Central Java which has got certification of malaria elimination in 2014 but again experience increased cases until 2016. Salaman I public health is an endemic malaria areas in Magelang regency. In 2016, 100 cases of malaria positive has found (API= 2.39/1000 inhabitants). This research aims to analyze the relationship between environmental factors toward malaria incidence in the region of Salaman I public health center by using the spatial approach. It is an observational analytical with case control study design. The sample of this research as much as 108 people consisting of 54 cases and 54 controls. Data analysis includes the univariate, bivariate, and spatial analysis. Chi-square test results showed that there is relationship between the habit of being outdoors at night (p = 0.041, OR = 2.340) and the use of mosquito-nets (p = 0.026, OR = 2.523) toward malaria incidence. Spatial analysis showed that the majority of malaria incidence is near the livestock cage, being around breeding place up to 400 m, and many found resting place in vicinity. The conclusion of this research is the habit of being outdoors at night and the use of mosquito-nets had relation with malaria incidence in the region of Salaman I public health center. It requires to distribute mosquito-nets evenly by the health agencies and the citizens should use long clothes and repellent especially when being outdoors at night.